Antibody Drug Conjugates in Lung Cancer. Issue 6 (November 2022) - Merle, Geoffrey; Friedlaender, Alex; Desai, Aakash; Addeo, Alfredo
Abstract: An antibody-drug conjugate (ADC) comprises a monoclonal antibody that is specific to a tumor cell protein, bound to a cytotoxic agent, known as the payload. The use of ADCs is already common practice in several cancers, thanks to their efficacy and potentially more manageable toxicity profile, resulting from the release of the cytostatic payload directly in the tumors. Currently, early-phase trials of ADCs in non–small cell lung cancer are rapidly gaining ground, with promising results targeting HER2 (human epidermal growth factor 2), HER3, TROP2 (trophoblast cell surface antigen 2), MET, CEACAM5 (carcinoembryonic antigen–related cell adhesion molecule 5), and PTK7 (tyrosine protein kinase–like 7). Unfortunately, in small cell lung cancer, trials targeting the ubiquitous DLL3 (delta-like ligand 3) protein have failed to show clinically relevant results, despite significant toxicity.